Disruption of lineage specification in adult pulmonary mesenchymal progenitor cells promotes microvascular dysfunction - Gaskill, Christa F. (J Clin Invest, 2017)
Pulmonary vascular disease is characterized by remodeling and loss of microvessels and is typically attributed to pathological responses in vascular endothelium or abnormal smooth muscle cell phenotypes. We have challenged this understanding by defining an adult pulmonary mesenchymal progenitor cell (MPC) that regulates both microvascular function and angiogenesis. The current understanding of adult MPCs and their roles in homeostasis versus disease has been limited by a lack of genetic markers with which to lineage label multipotent mesenchyme and trace the differentiation of these MPCs into vascular lineages. Here, we have shown that lineage-labeled lung MPCs expressing the ATP-binding cassette protein ABCG2 (ABCG2(+)) are pericyte progenitors that participate in microvascular homeostasis as well as adaptive angiogenesis. Activation of Wnt/β-catenin signaling, either autonomously or downstream of decreased BMP receptor signaling, enhanced ABCG2(+) MPC proliferation but suppressed MPC differentiation into a functional pericyte lineage. Thus, enhanced Wnt/β-catenin signaling in ABCG2(+) MPCs drives a phenotype of persistent microvascular dysfunction, abnormal angiogenesis, and subsequent exacerbation of bleomycin-induced fibrosis. ABCG2(+) MPCs may, therefore, account in part for the aberrant microvessel function and remodeling that are associated with chronic lung diseases.